2020
DOI: 10.1186/s12864-020-6647-4
|View full text |Cite|
|
Sign up to set email alerts
|

An analytical pipeline for identifying and mapping the integration sites of HIV and other retroviruses

Abstract: Background: All retroviruses, including human immunodeficiency virus (HIV), must integrate a DNA copy of their genomes into the genome of the infected host cell to replicate. Although integrated retroviral DNA, known as a provirus, can be found at many sites in the host genome, integration is not random. The adaption of linker-mediated PCR (LM-PCR) protocols for high-throughput integration site mapping, using randomly-sheared genomic DNA and Illumina paired-end sequencing, has dramatically increased the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 45 publications
(95 reference statements)
0
44
0
Order By: Relevance
“…The frequency and distribution of proviral DNA integration into genomic DNA was assessed by the linker-mediated PCR integration site assay ( Fig. 1 D ), incorporating a shearing step ( 2 , 4 ) to assess the relative frequency of descendants of single infected cells. In all, 202,179 and 524,691 total integration sites were mapped from donors 1 and 2, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and distribution of proviral DNA integration into genomic DNA was assessed by the linker-mediated PCR integration site assay ( Fig. 1 D ), incorporating a shearing step ( 2 , 4 ) to assess the relative frequency of descendants of single infected cells. In all, 202,179 and 524,691 total integration sites were mapped from donors 1 and 2, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DNA was sheared by sonication, and subjected to linker-mediated PCR and paired-end sequencing using an Illumina HiSeq platform. Results were analyzed according to established ISA workflows ( 2 , 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Total DNA was extracted from the PBMC two days following infection, which should not allow time for selection for, or against, proviruses integrated in specific sites or specific genes [29]. We used linker-mediated PCR [30] as previously described [21, 31] to identify IS. When we compared the global distribution of the IS from the PBMC obtained from the two individuals, the correlation coefficient was 0.98 and, for the rest of the analyses, we combined the data from the two sets of IS.…”
Section: Resultsmentioning
confidence: 99%
“…By combining in vivo IS from several studies [18, 21, 32, 33] (Table S1), we were able to assemble datasets comprising a total of 15,780 IS from pre-ART samples from 30 HIV-infected donors (hereafter referred to as “donors”) and 53,945 IS from on-ART samples from 39 donors (Table 1, S1). The introduction of a shearing step prior to linker ligation and PCR [30] creates different break points in flanking host DNA, making it possible to distinguish identical IS that arose by clonal expansion of a single infected cell [21, 30, 31]. After collapsing the IS with multiple breakpoints to a unique site, the two libraries contained 13,324 unique IS pre-ART and 33,336 unique IS on-ART (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that Additional file 1 was missing the supplemental figures (Figs. S1-S6) referenced in the file.…”
mentioning
confidence: 99%